2021
DOI: 10.1001/jama.2021.1640
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Headache

Abstract: IMPORTANCE Approximately 90% of people in the US experience headache during their lifetime. Migraine is the second leading cause of years lived with disability worldwide.OBSERVATIONS Primary headache disorders are defined as headaches that are unrelated to an underlying medical condition and are categorized into 4 groups: migraine, tension-type headache, trigeminal autonomic cephalalgias, and other primary headache disorders. Studies evaluating prevalence in more than 100 000 people reported that tension-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
20

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 112 publications
1
103
0
20
Order By: Relevance
“…Recently, Abdel Shaheed analyzed data from 36 publications and reported that paracetamol produced modest pain relief in hip and knee osteoarthritis, tension headache, and post-craniotomy pain and that it was ineffective in other conditions [ 145 ]; the authors concluded with the need for large, high-quality trials to reduce uncertainty about the efficacy of paracetamol in common pain conditions. In the last few months, new published studies report the safe use of paracetamol in patients with chronic kidney disease [ 147 ], the significant efficacy of paracetamol for post-arthroplasty pain [ 148 ], the lesser efficacy of paracetamol than ibuprofen for post-laminectomy pain [ 149 ], the opioid-sparing effects of paracetamol in the Emergency Department [ 150 ], the recommendations against paracetamol in lumbar spinal stenosis with neurogenic claudication [ 151 ], and the recommendations in favor of paracetamol for postcesarean pain [ 152 ] and for migraine [ 153 , 154 ].…”
Section: Recent Findings and Future Directionsmentioning
confidence: 99%
“…Recently, Abdel Shaheed analyzed data from 36 publications and reported that paracetamol produced modest pain relief in hip and knee osteoarthritis, tension headache, and post-craniotomy pain and that it was ineffective in other conditions [ 145 ]; the authors concluded with the need for large, high-quality trials to reduce uncertainty about the efficacy of paracetamol in common pain conditions. In the last few months, new published studies report the safe use of paracetamol in patients with chronic kidney disease [ 147 ], the significant efficacy of paracetamol for post-arthroplasty pain [ 148 ], the lesser efficacy of paracetamol than ibuprofen for post-laminectomy pain [ 149 ], the opioid-sparing effects of paracetamol in the Emergency Department [ 150 ], the recommendations against paracetamol in lumbar spinal stenosis with neurogenic claudication [ 151 ], and the recommendations in favor of paracetamol for postcesarean pain [ 152 ] and for migraine [ 153 , 154 ].…”
Section: Recent Findings and Future Directionsmentioning
confidence: 99%
“…The main differential diagnoses for migraine are tension-type headache and cluster headache [ 28 ]. Distinguishing features between these headache types include the typical location, quality, severity, and duration of pain, associated symptoms, and typical behaviour during attack, as shown in Figure 2 [ 32 ]. Briefly, tension headaches generally have mild-to-moderate, bilateral pain and lack migraine-associated symptoms (e.g.…”
Section: Common Barriers For Proper Migraine Diagnosis and Strategies To Overcome Themmentioning
confidence: 99%
“…Ditans are selective serotonin 5-HT 1F receptor agonists. In clinical trials as acute treatment, lasmiditan provided more benefit than placebo for freedom from headache pain and other associated symptoms including nausea, photophobia, and phonophobia 2 h after treatment [ 32 ]. Gepants and ditans are not thought to cause vasoconstriction and are not contraindicated in patients with cardiovascular disease or cardiovascular risk factors [ 42 ].…”
Section: A Contemporary Approach To Migraine Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine is one of the most common neurological diseases and affects one billion people globally 1. The past several years have seen the introduction of several new acute and preventive treatments for migraine, but patient and clinician interest in non-pharmacological treatments, including dietary changes, remains strong 23…”
mentioning
confidence: 99%